Use of Etonogestrel Implant Beyond Approved Duration – A Case Report - Castro Carvalho, C (2022)
The contraceptive implant is the most effective method of reversible contraception. Observational and trial data indicate that this method remains effective beyond the initially approved duration of use. We report a case of etonogestrel serum levels above the supposed threshold value for ovulation suppression nine years after implant insertion.